Broń i oporządzenie jeździeckie w inwentarzach mieszczan krakowskich z drugiej połowy XV wieku - Wilk-Woś, Zofia (Acta Universitatis Lodziensis. Folia Historica, 2001)
The following article is an attempt to analyse and interpret the weaponry and other elements of equestrian gear, which were recorded in XVth century inventories of Kraków citizens. The paper discusses offensive and defensive armaments and equipment while interpreting German, Latin and Polish terms and assessing an approximate value of the above-mentioned objects. Subsequently, the article explains the reasons for including weaponry in the inventories. The analysis of the movable items has shown that the weaponry is characteristic of the inventories which are more exhaustive in terms of quality as well as quantity of contents. The weaponry groups display both uniformity (they show wide use of cross-bows and sword, and, as lar as the defensive weapon is concerned, helmets, coats of mail and metal plates) and differentiation. Weapon kits confirm a good preparation of Kraków citizens for military assaults. It should be remembered that the above-mentioned documents concern mostly the wealthiest stratum of Kraków inhabitants, who could afford the purchase of the appropriate weapons. It has also been concluded, that the appearance of weaponry in the inventories of movables was connected with military duties of the citizens. The presence of weaponry, especially in the case of the reach merchants and council members, might have resulted from the necessity of defending the possessed wealth and it thought to have given the proprietor a feeling of personal security.